Case Report: Successful treatment of severe fever with thrombocytopenia syndrome associated with hemophagocytic lymphohistiocytosis by preemptively using favipiravir and methylprednisolone - Liang Qiao; Liang Qiao; Liang Qiao; Liang Qiao; Ting-juan Zhang; Ting-juan Zhang; Ting-juan Zhang; Ting-juan Zhang; Yuan Feng; Yuan Feng; Yuan Feng; Yuan Feng; et al. (Frontiers in Medicine)
BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by a novel Bunyavirus with a high mortality rate. Cytokine storm could be regarded as an important feature of SFTS patients. Severe or critical cases of SFTS are often complicated with the presence of hemophagocytic lymphohistiocytosis (HLH), resulted in rapid disease progression and extremely adverse prognosis. Currently, effective treatments for these severe cases remain unavailable. Herein, we reported a case of SFTS associated with HLH successfully treated by favipiravir and methylprednisolone.Case presentationA 73-year-old male farmer was admitted to our hospital with a fever, fatigue, and bicytopenia for 1 week on June 20, 2024. The patient had a history of farm work. The diagnosis of SFTS was confirmed by detection of Bunyavirus RNA in the blood samples. Bone marrow examination revealed marked infiltration of macrophages with hemophagocytosis in the bone marrow leading to a diagnosis of HLH. Notably, the patient was preemptively treated with favipiravir together with methylprednisolone and supportive therapy before the diagnosis of SFTS associated with HLH. Excitingly, the patient was recovered after 10 days treatment.ConclusionEarly recognition of SFTS complicated with HLH is particularly important, and the preemptive application of favipiravir may improve the prognosis of these patients.